2022
DOI: 10.1007/s10479-022-04771-8
|View full text |Cite|
|
Sign up to set email alerts
|

Malmquist productivity indices and plant capacity utilisation: new proposals and empirical application

Abstract: The purpose of this contribution is to compute the popular Malmquist productivity index while adding a component representing plant capacity utilisation. In particular, this is—to the best of our knowledge—the first empirical application estimating both input- and output-oriented Malmquist productivity indices in conjunction with the corresponding input- and output-oriented plant capacity utilisation measures. Our empirical application focuses on a provincial data set of tourism activities in China over the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…In the contemporaneous setting of efficiency analysis, such differences have been empirically observed for value functions (Ang et al, 2018; Kerstens & Van de Woestyne, 2021) and distance functions (Kerstens, 1996). In the intertemporal setting of productivity change, several studies report differences (Ang & Kerstens, 2017; Kerstens et al, 2022, 2018), although there can be special cases of equivalence (Ang et al, 2023). The differences between convex and nonconvex estimates for the components of BLHM $BLHM$ remain to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In the contemporaneous setting of efficiency analysis, such differences have been empirically observed for value functions (Ang et al, 2018; Kerstens & Van de Woestyne, 2021) and distance functions (Kerstens, 1996). In the intertemporal setting of productivity change, several studies report differences (Ang & Kerstens, 2017; Kerstens et al, 2022, 2018), although there can be special cases of equivalence (Ang et al, 2023). The differences between convex and nonconvex estimates for the components of BLHM $BLHM$ remain to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the economic downturn had major negative effects on hotel productivity for two years (2008 and 2009). Please refer to Chatzimichael and Liasidou (2019), Kerstens et al, (2022) for more references.…”
Section: Efficiency Measurement In Tourism Sectormentioning
confidence: 99%